2018
DOI: 10.1016/j.thromres.2018.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Management of anticoagulation for cancer-associated thrombosis in patients with thrombocytopenia: A systematic review

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Lower thrombotic risk scenarios where full-dose anticoagulation may not be justified include non-acute VTE (especially in autologous hematopoietic stem cell transplantation), catheter-related thrombosis and low risk atrial fibrillation [ 114 , 125 , 126 , 129 ]. Strategies for mitigating the high bleeding risk associated with continued anticoagulation include increased platelet transfusion threshold (e.g., 40–50 × 10 9 /L) and anticoagulation dose reductions, but evidence proving the safety and efficacy of both approaches is lacking [ 130 ].…”
Section: Managing Antithrombotic Therapy In Thrombocytopenic Patiementioning
confidence: 99%
“…Lower thrombotic risk scenarios where full-dose anticoagulation may not be justified include non-acute VTE (especially in autologous hematopoietic stem cell transplantation), catheter-related thrombosis and low risk atrial fibrillation [ 114 , 125 , 126 , 129 ]. Strategies for mitigating the high bleeding risk associated with continued anticoagulation include increased platelet transfusion threshold (e.g., 40–50 × 10 9 /L) and anticoagulation dose reductions, but evidence proving the safety and efficacy of both approaches is lacking [ 130 ].…”
Section: Managing Antithrombotic Therapy In Thrombocytopenic Patiementioning
confidence: 99%
“…Multiple retrospective, single‐center cohort studies reported results on the management of CAT and thrombocytopenia, all with LMWH [34]. In general, regimens incorporated dose reduction or temporary holding of LMWH, depending on platelet count.…”
Section: Thrombocytopeniamentioning
confidence: 99%
“…Unfortunately, randomized comparisons are not available, and clinicians are left with only retrospective case series and small, observational cohort studies to guide clinical decision‐making . A recent systematic review of the literature failed to identify any evidence for superiority of one method over another .…”
Section: Background and Available Evidencementioning
confidence: 99%